Representation of Gender Ideology in Indonesia Novels: A Study of The Reformation Era Novel - Yulianeta Yulianeta; Siti Chamamah Soeratno; Juliasih Kusharyanto (Lingua Cultura, 2016)
This research was based on a phenomenon that gender ideology practiced by a society might be reflected in the production of literary work. Thus, even though a novel is known as an imaginative work, its content and gender ideology could not be detached from social reality. The aims of this research were describing the role and gender identity, the types of gender ideology, and the gender relationship issues in the Indonesia novel written during reformation era. Gramsci’s theory of hegemony and gender perspective helped to describe the problems presented in this article. The formal object of this research was elaborating gender ideology presented in four novels written by Indonesian authors during reformation era, namely Saman by Ayu Utami, GeniJora by Abidah El Khalieqy, Nayla by Djenar Maesa Ayu, and Tanah Tabu by Anindita S. Tayf. The research method implemented was library research. This research showed the variety of ideologies that occupy literature as the site of struggle among ideologies. The results of the research are the four novels represent the patriarchal ideology, familialism ideology, ibuism ideology, and general gender ideology. The four gender ideologies create domestication of the position and the role of women. The existence and the organization of the gender ideology are supported by masculine hegemony in Indonesian culture.